Generic music style preferences of urban South African adolescents : a follow-up study including additional genres of Hip-Hop, House, Kwaito, Metal and Rhythm&Blues - Van Niekerk, Caroline (University of Pretoria, 2013)
Dissertation (MMus)--University of Pretoria, 2011.